Antifungal Activity of the Essential Oil of Cymbopogon citratus (DC) Stapf. An in vitro study. - Leite Cavalcanti, Alessandro (Journal of Oral Research, 2019)
Aim. To evaluate the antifungal potential of the essential oil of Cymbopogon citratus by determining the Minimum Inhibitory Concentration (MIC) and the Minimum Fungicidal Concentration (MFC) for Candida albicans(ATCC 90029), Candida albicans (CBS 562), Candida tropicalis (ATCC 705) and Candida tropicalis strains (CBS 94), as well as to analyze the possible mechanism of action of the oil through the addition of sorbitol to the culture medium. Methods. For the MIC determination, inocula were previously adjusted through spectrophotometry and 100?L were added to the wells of plates already containing the culture medium and 100?L of the serial dilutions of the oil, incubating them in aerobiosis for 24 hours, with subsequent staining by 1% TCT. For the MFC, 50?L of the supernatant from the MIC assay wells were dripped onto Petri dishes and incubated in aerobiosis for 24 hours. Tests were performed in triplicate and data analysed by descriptive statistics. Results. It was determined that the MIC for Candida albicans was 125 ?g/mL while MIC for Candida tropicalis was 250?g/mL, with the essential oil presenting fungicidal effect for both analyzed yeasts. Conclusion. The essential oil of Cymbopogon citratus does not act at the cellular wall level and demonstrated an antimicrobial effect on Candida albicans and Candida tropicalis, therefore acting as a fungicide.